Payment by results and social impact bonds : outcome-based payment systems in the UK and US - Albertson, Kevin, 1963-; Fox, Chris (Policy Press shorts. Research., 2018)
As public services budgets are cut, the 'Payment by Results' (or Pay for Success) model has become a popular choice in public sector commissioning. Social Impact Bonds are a variant of Payment by Results also promoted by proponents of social (or impact) investing. But how effective are these approaches? This short book asks whether the Payment by Results model is an efficient way to unlock new capital investment, help new providers to enter the 'market' and foster innovation, or whether the extension of 'neoliberal' thinking, complexity and the effects of managerialism undermine the effective delivery of social outcomes.